2003
DOI: 10.1590/s0074-02762003000700005
|View full text |Cite
|
Sign up to set email alerts
|

First report of Lymnaea columella Say, 1817 (Pulmonata: Lymnaeidae) naturally infected with Fasciola hepatica (Linnaeus,1758) (Trematoda: Digenea) in Argentina

Abstract: We report the first evidence of natural infection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 9 publications
0
18
0
5
Order By: Relevance
“…However, all Venezuelan samples collected in this study are morphologically similar to susceptible phenotypes studied in Cuba, i.e., well rounded shell and characteristic mantle pigmentation pattern (Gutiérrez et al 2003). Moreover, L. columella has been reported naturally infected by F. hepatica in several countries it has invaded, such as Australia (Boray et al 1985), Brazil (Ueta 1980) and Argentina (Prepelitchi et al 2003).…”
Section: Role Of Lymnaeid Snails In the Transmission Of Fascioliasis mentioning
confidence: 99%
“…However, all Venezuelan samples collected in this study are morphologically similar to susceptible phenotypes studied in Cuba, i.e., well rounded shell and characteristic mantle pigmentation pattern (Gutiérrez et al 2003). Moreover, L. columella has been reported naturally infected by F. hepatica in several countries it has invaded, such as Australia (Boray et al 1985), Brazil (Ueta 1980) and Argentina (Prepelitchi et al 2003).…”
Section: Role Of Lymnaeid Snails In the Transmission Of Fascioliasis mentioning
confidence: 99%
“…In Brazil, L. columella showed the following infection rates: 2.4% in Rio de Janeiro (Rezende et al 1973); 5.2 and 3.9% in Minas Gerais (Coelho & Lima 2003); 1.22 and 0.14% (Ueta 1980), 5.26% (Oliveira et al 2002) in São Paulo; 3.3% in Rio Grande do Sul (Silva Santos et al 1987). In Corrientes, Argentina, the prevalence of L. columella was 8.8% (Prepelitchi et al 2003). In central France, Rondelaud et al (2001) reported a global prevalence of natural infection of 1.1% in L. truncatula and 0.3% in L. glabra.…”
mentioning
confidence: 99%
“…Las característi-cas del sistema radular (Larrea et al, 1994; Hurtado y Tantaleán, 1998), así como las evaluaciones morfológicas del aparato reproductor (Larrea et al, 1993;Prepelitchi et al, 2003) demostraron la presencia de Lymnaea viatrix y Pseudosuccinea columella. Este hallazgo difiere con lo observado por Larrea et al (1994), quienes no hallaron al caracol Pseudosuccinea columella en la zona de Cusco y Puno, tal vez debido a que estos autores no evaluaron zonas altas como en el presente estudio o probablemente este hallazgo confirma la introducción de esta especie a nuevos hábitats.…”
Section: Discussionunclassified